2018
DOI: 10.1128/jb.00180-18
|View full text |Cite
|
Sign up to set email alerts
|

Activity of a Holin-Endolysin System in the Insecticidal Pathogenicity Island of Yersinia enterocolitica

Abstract: is a pathogen that causes gastroenteritis in humans. Because of its low-temperature-dependent insecticidal activity, it can oscillate between invertebrates and mammals as host organisms. The insecticidal activity of strain W22703 is associated with a pathogenicity island of 19 kb (Tc-PAI ), which carries regulators and genes encoding the toxin complex (Tc). The island also harbors four phage-related and highly conserved genes of unknown functions, which are polycistronically transcribed. Two open reading frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Deliberate overproduction of the Y. enterocolitica W22703 holin and endopeptidase in E. coli was shown to result in cell lysis (Springer et al, 2018), which has also been observed when ChiW/ChiX are highly overproduced (Owen, 2016). However, in the native context S. marcescens DB10 chiW and chiX expression is carefully regulated (Hamilton et al, 2014), presumably to prevent the uncontrolled accumulation of these proteins to levels could induce lysis, and this also appears the case for the Y. enterocolitica system (Springer et al, 2018). This underscores the importance of studying the function of these proteins produced at native levels under physiological conditions wherever possible.…”
Section: A Holin/ L-ala D-glu Endopeptidase Pairing Is Conserved Acmentioning
confidence: 93%
See 3 more Smart Citations
“…Deliberate overproduction of the Y. enterocolitica W22703 holin and endopeptidase in E. coli was shown to result in cell lysis (Springer et al, 2018), which has also been observed when ChiW/ChiX are highly overproduced (Owen, 2016). However, in the native context S. marcescens DB10 chiW and chiX expression is carefully regulated (Hamilton et al, 2014), presumably to prevent the uncontrolled accumulation of these proteins to levels could induce lysis, and this also appears the case for the Y. enterocolitica system (Springer et al, 2018). This underscores the importance of studying the function of these proteins produced at native levels under physiological conditions wherever possible.…”
Section: A Holin/ L-ala D-glu Endopeptidase Pairing Is Conserved Acmentioning
confidence: 93%
“…It has been shown that these two regulators control toxin induction in Yersinia enterocolytica strain W22703 at low temperatures (Starke et al, 2013). More recently, it was reported that the holin/endopeptidase/ spanin genes in the cluster are transcriptionally coupled, and that expression of these genes is exceptionally low (Springer et al, 2018).…”
Section: A Holin/ L-ala D-glu Endopeptidase Pairing Is Conserved Acmentioning
confidence: 99%
See 2 more Smart Citations
“…ElyY revealed an endopeptidase with high substrate specificity that cleaves yersinial murein. We also demonstrated that upon overexpression, the dual lysis cassette is able to lyse cells of E. coli and of several, but not all, Yersinia species including Y. enterocolitica and Y. pseudotuberculosis (15). Remarkably, HolY and ElyY lyse Y. enterocolitica at body temperature, but not at 15°C.…”
Section: Introductionmentioning
confidence: 81%